(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
As a rule, the standard treatment of most purulent-inflammatory diseases of the maxillofacial region involves surgical intervention followed by the use of antibacterial and symptomatic therapy. At the same time, they do not always resort to the correction of immunometabolic disorders with the help of drugs and physiotherapeutic methods of treatment.